2021
DOI: 10.1016/j.cophys.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory deafferentation reveals lateralized roles of proprioception in feedback and adaptive feedforward control of movement and posture

Abstract: Proprioception provides crucial information necessary for determining limb position and movement and plausibly also for updating internal models that might underlie the control of movement and posture. Seminal studies of upper-limb movements in individuals living with chronic, large-fiber deafferentation have provided evidence for the role of proprioceptive information in the hypothetical formation and maintenance of internal models to produce accurate motor commands. Vision also contributes to sensorimotor fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The role of proprioception in motor control has been well documented, notably for postural stability, motor coordination, and fine motor skills (Gandevia & Burke, 1992;Pearson, 2001;Scott, 2016). The role of proprioception with and without visual feedback has been well-illustrated by the consequences of proprioceptive loss on motor functions (Jayasinghe et al, 2021;Rothwell et al, 1982;Sarlegna et al, 2006Sarlegna et al, , 2010. Considering the critical role of proprioception in the perception and control of postures and movements and considering the body's widespread proprioceptors, a key question is "Is proprioception uniform across the body?…”
Section: Introductionmentioning
confidence: 99%
“…The role of proprioception in motor control has been well documented, notably for postural stability, motor coordination, and fine motor skills (Gandevia & Burke, 1992;Pearson, 2001;Scott, 2016). The role of proprioception with and without visual feedback has been well-illustrated by the consequences of proprioceptive loss on motor functions (Jayasinghe et al, 2021;Rothwell et al, 1982;Sarlegna et al, 2006Sarlegna et al, , 2010. Considering the critical role of proprioception in the perception and control of postures and movements and considering the body's widespread proprioceptors, a key question is "Is proprioception uniform across the body?…”
Section: Introductionmentioning
confidence: 99%
“…Handedness is a particular aspect of motor control referring to the preferential employment of a hand -the dominant one -to perform daily-life tasks. Asymmetries in the neural organization of cerebral hemispheres could explain inter-limb differences in the control of arm movements (Carson et al 1992;Flowers 1975;Jayasinghe et al 2021;Roy et al 1994;Roy and Elliott 1986;Sainburg 2002Sainburg , 2014Woytowicz et al 2018). A large body of literature suggests that the dominant arm/hemisphere is specialized for open-loop optimization-like processes, whilst the non-dominant arm/hemisphere is specialized for closed-loop control that stabilized arm postures against unexpected environmental conditions (Bagesteiro and Sainburg 2002;Sainburg 2002;Schaffer and Sainburg 2017;Sainburg 2011, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that damage to the left hemisphere led to deficits in trajectory control, whereas as damage to the right hemisphere led to deficits in final position control. More recently, studies on somatosensory deafferentation also revealed lateralized roles of proprioceptive feedback (Jayasinghe et al, 2020(Jayasinghe et al, , 2021, with the right arm failing to stabilize at the end-point of the reaching movement and the left arm showing poor corrections of the trajectory. However, other results have shown that the two arms can develop feedforward adaptation equally well in an experiment in which participants performed fast straight reaching movements, with similar force fields to our experiments (Reuter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%